Conception of ecological strategy «Olympic sport for maintainance of nature» during leadthrough of winter Olympic Games 2022 in Ukrainian Carpathians - Tsyganenko O.I; Sklyarova N.A; Persheguba Y. V.; Oksamitnaya L. F.; Putro L.M (Kharkov National Pedagogical University, 2012)
An analysis is conducted scientific and to scientifically-methodical literatures on issue of ecological strategy of organization and leadthrough of winter Olympiads. Conception of ecological strategy of organization and leadthrough of winter Olympiad is developed 2022 (Ukraine, Carpathians). It was offered, that ecological strategy of organization and leadthrough of Olympiad had an ecological motto «Olympic sport for the maintainance of nature». Strategy included the ways of decision of problem of negative influence of global change of climate on the olympic winter types of sport. The problems of providing of ecological safety of sporting activity are considered in relation to a man and wild-life. Solution is offered questions of the ecological marketing, management and ecological inlightening. The ecological ground of choice of Lvov is conducted as a city of organizer of winter Olympiad 2022. As a mountain-skier center a mountain-skier complex Borzhava, located in the area Carpathians of Ukraine, is offered.